2001
DOI: 10.1097/00007632-200104010-00025
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Radiation Before Surgical Decompression Adversely Affects Outcomes of Surgery for Symptomatic Metastatic Spinal Cord Compression

Abstract: Spinal radiation before surgical decompression for metastatic spinal cord compression is associated with a significantly higher major wound complication rate. In addition, preoperative spinal irradiation might adversely affect the surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
2
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(134 citation statements)
references
References 23 publications
4
122
2
6
Order By: Relevance
“…Similar to the series of McDonnell et al, we found a higher incidence of complications when using a combined approach, but this did not hold true in the multivariate analysis. It has been reported that preoperative radiotherapy increases wound infection and tissue breakdown rate, particularly after surgery by a posterior approach [18,38,51]. In our series, prior history of spinal irradiation was not a risk factor for the development of wound infections.…”
Section: Complicationssupporting
confidence: 41%
“…Similar to the series of McDonnell et al, we found a higher incidence of complications when using a combined approach, but this did not hold true in the multivariate analysis. It has been reported that preoperative radiotherapy increases wound infection and tissue breakdown rate, particularly after surgery by a posterior approach [18,38,51]. In our series, prior history of spinal irradiation was not a risk factor for the development of wound infections.…”
Section: Complicationssupporting
confidence: 41%
“…Complications may occur in up to 25% of patients who undergo surgery for spinal metastases, the most common being wound infection [13,17,38]. Life expectancy is usually determined by the overall extent of the metastatic disease and, therefore, to be of benefit, surgery must improve quality of life.…”
Section: Recommendations Of the Gstsgmentioning
confidence: 99%
“…Wound complications (32%) were observed when radiotherapy took place before surgery compared with 12% if surgery was the first-line treatment (Po0.05). 25 Rehabilitation care contract When life expectancy conditions the PM&R care, the contract defines right away the limits of the patients rehabilitation stay. This contract goes beyond the patients' sole judgments and wishes even though their needs and expectations are taken into account.…”
Section: Associated Symptomsmentioning
confidence: 99%